Avoiding the ballistocardiogram (BCG) artifact of EEG data acquired simultaneously with fMRI by pulse-triggered presentation of stimuli - Ertl, Matthias; Kirsch, Valerie; Leicht, Gregor; Karch, Susanne; Olbrich, Sebastian; Reiser, Maximilian; Hegerl, Ulrich; Pogarell, Oliver; Mulert, Chistoph (Journal of neuroscience methods, 2010)
Simultaneous acquisition of electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) data could offer a much deeper understanding of brain function, e.g. in the analysis of tempo-spatial dynamics of brain activity in cognitive processing. However, more sophisticated analysis methods such as single-trial coupling of EEG and fMRI are often handicapped by the limited quality of EEGs acquired in the MRI scanner. In particular, the ballistocardiogram (BCG) artifact is still a relevant problem. Methods that are currently available typically remove the BCG artifact either in post-recording or real-time signal processing. Here, we would like to suggest a new strategy to avoid BCG artifacts during data acquisition. In our proposal, stimuli are presented pulse-triggered (PT), thus avoiding interference of BCG artifacts with the evoked potentials investigated during EEG recording. This method is based on the observation that the main influence of the BCG artifact is generally limited to the time interval of 150–500 ms post-QRS complex. Based on real measurements, we simulated different signal presentation methods relative to the onset of the BCG artifact for 14 subjects. Stimuli were either presented independently of the BCG artifact or pulse-triggered at fixed time-points (280 ms, 480 ms and 680 ms post-QRS complex) and with a jitter (short: 120 ms or long: 240 ms). In combination with an averaged artifact subtraction method signal distortion was reduced at best by 47%.